Police Policy In Using Restorative Justice Methods Against Child Criminal Actors - Indrayana, Indrayana (CV. Inara, 2022)
Children as the nation's buds in building the nation and state for the future of the child itself. restorative justice is an approach that focuses on the conditions for creating justice and balance for the perpetrators of criminal acts and their victims. The mechanism for criminal justice procedures focusing on sentencing is transformed into a process of dialogue and mediation to create an agreement on a more just and balanced settlement for victims and perpetrators.Problems 1. How is the Implementation of Police Policy in the Use of Restorative Justice Methods Against Child Criminal Actors? with descriptive-analytical research specifications and sources of secondary and primary data. the results of police policy research in using the method of restorative justice against perpetrators of child crimes, police policies in carrying out settlement efforts through mediation and recovery consultations with non-punitive decisions prioritizing solutions in the best interests of the perpetrators, victims, and the community. The policy of the Police of the Republic of Indonesia is to issue a Circular Letter of the Police of the Republic of Indonesia Number: 8 of 2021 concerning the Application of Restorative Justice. prioritizing the interests of the victim and the perpetrator in order to reach an agreement together to seek a solution to the crime by emphasizing on recovery, not retaliation. It is through law enforcement that this becomes a reality. However, in enforcing the law there are 3 (three) elements that need to be considered, namely: legal certainty, expediency and justice.